Enriching the 1758 Portuguese Parish Memories (Alentejo) with Named Entities. (9th September 2021) - Vieira, Renata; Olival, Fernanda; Cameron, Helena Freire; Santos, Joaquim; Sequeira, Ofélia; Santos, Ivo
This work presents an enriched version of the Parish Memories (1758–1761), an essential Portuguese historical source manually transcribed. It is enriched with annotations of named entities of the types PERSON, LOCATION, and ORGANIZATION. The annotation was done automatically for the whole collection where two researchers annotated a portion of it manually for evaluation purposes. In this dataset, we provide the tagged texts, the lists of extracted entities, and frequency counts. The corpus is useful for historians, allowing, for instance, comparative analyses between parishes and regions or to calculate the area of influence of a locality. The paper describes the creation and evaluation of the corpus, discusses its applications and limitations. This first release may be improved by other researchers interested in the historical source itself or in the technology employed in its annotation.